HUBUNGAN PEMBERIAN KOMPRES POVIDONE IODINE TERHADAP KESEMBUHAN LUKA GANGREN DI RSUD DR. R. SOEPRAPTO CEPU KABUPATEN BLORA - A.Maftukhin, A.Maftukhin; Ainu Zuhriyah, Ainu Zuhriyah; Indriana Listiyobudi, Indriana Listiyobudi (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2013)
Wound care is generally done by replacing wear a bandage and clean the wound antiseptic solution such as povidone iodine . The purpose of this study was to determine the relationship of the administration of povidone iodine compresses gangrenous wound healing in dr . R. Suprapto Cepu Blora. This study uses the correlational analytic methods , the cross-sectional approach . The population is patients with gangrenous wounds in dr . R. Soeprapto Cepu , an average of 23 people . The sample is a portion of patients with gangrenous wounds, as many as 18 people . The sampling technique accidental sampling . Retrieval of data by observation , then in editing , coding ,scoring, tabulating , cross table . The results of the study of 18 respondents , 9 respondents who do compress povidone iodine , 8 people ( 88.9 % ) rapid wound healing , and 9 respondents that do not compress povidone iodine , 7 ( 77.8 % ) slow wound healing . From the results of Table Cross , found no association with the administration of povidone iodine compresses gangrenous wound healing . The conclusion of this study is that there is a relationship between the administration of povidone iodine compresses with gangrenous wound healing . Nurses are advised not only to use povidone iodine solution but also use saline solution to wash the wound in the wound healing process and provide counseling to family members of patients to participate in the care of patients with gangrenous wound by providing appropriate nutritional needs of patients such as those provided gangrenous wounds hospital that is rich in protein , carbohydrates , fats , vitamins , and mineralKeywords : Povidone Iodine , gangrenous wounds